Social Solidarity And Community Integration Through Sport: A Systematic Literature Review - Silatul Rahmi; M. Imran Hasanuddin (Journal Physical Health Recreation (JPHR), 2025)
Sport has an important role in strengthening social relationships amid the increasing individualism and fragmentation of modern society. In this context, this research was conducted to examine how sport contributes to the formation of social solidarity and community integration. The main objective of this study is to identify the social mechanisms formed through sports activities and understand their relevance to the development of social cohesion of the community. This study uses the Systematic Literature Review (SLR) method which refers to the PRISMA guidelines, by analyzing ten scientific articles published between 2015 and 2025. Data was obtained through a systematic selection from Google Scholar, Scopus, and ScienceDirect databases, then analyzed using a thematic approach. The results of the study show that sports function as a means of forming social solidarity, a medium for cross-social and cultural integration, as well as a forum for the formation of social capital and collective identity. Sports activities have been proven to strengthen a sense of community, trust, and inclusive values that support social cohesion. In conclusion, sport has great potential as a social instrument to strengthen community integration and build harmonious communities. Further research is suggested using empirical and longitudinal approaches to measure the long-term impact of sport on social solidarity.